Residential fungal β-(1,3)-D-glucan exposure is associated with decreased pulmonary function in fibrotic pulmonary sarcoidosis. - Stapleton, Emma M; Metwali, Nervana; Shlossman, Michael; Wendt, Linder; Pezzulo, Alejandro A; Hamzeh, Nabeel Y; Comellas, Alejandro P; Thorne, Peter S; Gerke, Alicia K (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Sarcoidosis is a multi-system disease frequently affecting the lungs. It is thought to be mediated by gene-environment interaction; for example, epidemiological data show organic aerosol exposure increases risk of pulmonary sarcoidosis. The aim of this study was to assess whether exposure to bioaerosol associates with worse lung disease in patients with pulmonary sarcoidosis.Methods: Using an observational, cohort study design, we measured residential exposure to fungal and bacterial cell wall material, β-(1,3)-D-glucan (BDG) and endotoxin, respectively, in healthy control subjects and those with pulmonary sarcoidosis. In the case cohort, we compared bioaerosol concentrations to pulmonary disease severity, assessed by pulmonary function testing, qualitative chest computed tomography (CT), and serum biomarkers. Log-transformed bioaerosol concentrations were compared to lung function and significance and correlation determined by Pearson correlation.Results: Homes of subjects with sarcoidosis had higher BDG and endotoxin concentrations than control subjects. Patients with significant pulmonary fibrosis had greater disease severity (Wasfi severity score, visual analogue scale) and reduced pulmonary function compared to those without fibrosis (all P